1993
DOI: 10.1063/1.464303
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian basis sets for use in correlated molecular calculations. III. The atoms aluminum through argon

Abstract: Correlation consistent and augmented correlation consistent basis sets have been determined for the second row atoms aluminum through argon. The methodology, originally developed for the first row atoms [T. H. Dunning, Jr., J. Chem. Phys. 90, (1989)] is first applied to sulfur. The exponents for the polarization functions (dfgh) are systematically optimized for a correlated wave function (HF+ 1+2). The (sp) correlation functions are taken from the appropriate HF primitive sets; it is shown that these functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
5,159
4
44

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9,062 publications
(5,243 citation statements)
references
References 17 publications
36
5,159
4
44
Order By: Relevance
“…Full counterpoise correction was used throughout. The cc-pVTZ basis set [76,77] was applied in these calculations. Density-fitting (DF) approximations [78,79] were used for both the Hartree-Fock and the correlation part, with the corresponding cc-pVTZ/JKFIT [80] and ccpVTZ/MP2FIT [81] auxiliary basis sets, respectively.…”
Section: Lccsd(t0) Pmisp Calculationsmentioning
confidence: 99%
“…Full counterpoise correction was used throughout. The cc-pVTZ basis set [76,77] was applied in these calculations. Density-fitting (DF) approximations [78,79] were used for both the Hartree-Fock and the correlation part, with the corresponding cc-pVTZ/JKFIT [80] and ccpVTZ/MP2FIT [81] auxiliary basis sets, respectively.…”
Section: Lccsd(t0) Pmisp Calculationsmentioning
confidence: 99%
“…Calculations were performed for sodium bromide, the results of which are shown in Table 1 together with other prominent results from the literature. 53 Utilizing the core-valence basis sets developed by Dunning et al for bromine 39,40 Results from the literature shown in Table 1 also show that the inclusion of electron correlation has the effect of shortening the sodium-bromine bond. The DFT results underestimate the monomer value when compared with the microwave value.…”
Section: Resultsmentioning
confidence: 96%
“…The success of the EXPRESS method (applied to sodium chloride) 3 were obtained employing the core-valence basis set of Martin et al 38 for the sodium atom and the equivalent basis set by Dunning 39,40 for the chlorine atom. These basis sets allow for higher orders of angular momentum in the traditional 'core' region, which is required when more than just the standard valence electrons are used in the correlation scheme.…”
Section: Introductionmentioning
confidence: 99%
“…The B3LYP hybrid method with the aug-cc-pVDZ basis set [46,47] was used for most atom types, with the aug-ccpVDZ-PP [48,49] pseudopotential basis set used for the heavy bromine atoms in 4.…”
Section: Methodsmentioning
confidence: 99%